Information, Switching Costs, and Consumer Choice: Evidence from Two Randomized Field Experiments in Swedish Primary Health Care - Anders Anell; Jens Dietrichson; Lina Maria Ellegård; Gustav Kjellsson (Lund University, School of Economics and Management, Department of Economics, 2018)
Consumer choice of services that are financed by a third party may improve the matching of consumers and providers, and spur competition over quality dimensions relevant to consumers. However, in markets characterized by information frictions and switching costs, the gains from choice may fail to materialize. We use two large-scale randomized field experiments in primary health care to examine if leaflets with comparative information and pre-paid choice forms sent to consumers by postal mail affect choices. The results demonstrate that there are demand side frictions in the primary care market and indicate how these frictions can be mitigated.
Keywords: D83; I11; I18; 330; Consumer choice; Information; Switching costs; Primary health care; Field experiments